Language rights in education in South Africa - Mkhize, D.; Balfour, R. (South African Journal of Higher Education, 2017)
Realisation of multilingual education as a right has remained a controversial issue in South Africa. This is despite the Constitutional and legislative frameworks that support multilingual education. While the controversy undermines linguistic diversity in educational institutions in general, as suggested by the exclusion of African languages in the curriculum in some primary schools, it is in the curriculum of most institutions of higher learning where this linguistic diversity is undermined. Despite this bleak picture, some studies report promising trends regarding attempts at promoting multilingual education in some of these institutions. The article concludes by encouraging the universities to interrogate the language ideologies that underlie the language policies and implementation of the policies in the institutions of higher learning, and how these promote or infringe the language rights of students.